Essential Trace Element Status in Foreign First-Year Students Attending RUDN University - Kirichuk, Anatoly A.; Skalny, Rey A.; Butnaru, Denis V.; Zhuchenko, Natalia A.; Tinkov, Alexey A.; Skalny, Anatoly V. (Pakistan Journal of Nutrition, 2021)
Background and Objective: Micronutrient deficiency is characterized by strong geographic patterns. The objective of the present study was to perform comparative analysis of essential trace elements levels in hair and urine of Russian and foreign first-year students attending the Peoples’ Friendship University of Russia (RUDN University, Moscow). Materials and Methods: The study involved 65 first-year RUDN University students from Russia as well as 207 foreign first-year students from Asia, Middle East, Africa and Latin America. Evaluation of hair and urinary copper (Cu), iron (Fe), iodine (I), selenium (Se) and zinc (Zn) content was performed using inductively-coupled plasma mass-spectrometry. Results: Hair Cu content in Russian students was found to be higher than that in examinees from Asia and Middle East by 25 and 32%, respectively. Hair Fe content in students from Asia, Middle East and Latin America were 30, 66 and 29% lower when compared to the control values. The hair iodine levels in the students from Middle East were lower than those of Russia, Asia, Africa and Latin America by a factor of 3.4, 3.6, 5.5 and 4.7 respectively. The highest hair Se levels were observed in Asian students. Hair Zn content in African students was found to be lower than that in Russian, Asian, Middle East and Latin American counterparts by 30, 30, 26 and 16%, respectively. Urinary metal levels partially corresponded to the observed patterns in hair. Zn excretion tended to be higher in all foreign students when compared to the Russian values. However, no significant group difference in urinary iodine levels were observed. Conclusion: The results correspond to the geographic patterns of the prevalence of micronutrient deficiency. Monitoring and modulation of nutritional trace element status may improve health and educational performance in students.